Представления о браке и брачном партнере у молодых людей, воспитывавшихся в неполной семье - Яворовская, Л.Н.; Моря, Е.В. (My University, 2011)
Анотація В статті розглянуто розлучення батьків на наступний розвиток та формування особистості дитини. проаналізовано данні емпіричного дослідження уявлень щодо шлюбу та шлюбного партнеру молодими людьми, що мали досвід розлучення батьків. Ключові слова: уявлення про шлюб, розлучення батьків, неповна сім’я, шлюбний партнер. Annotation Perceptions of Marriage and Marriage Partner Among Young People Brought Up in Incomplete Families The article considers how parents’ divorce on further forming of child’s personality. Results of experimental research of marriage nation and marriage partners of young people who suffered parents’ divorce were analyzed. Keywords: understanding of marriage, divorce of parents, incomplete family, a marriage partner
Keywords: шлюбний партнер; уявлення про шлюб; розлучення батьків; неповна сім’я